Adsorption of Cadmium By Silica Chitosan - Moftah Ali; Ani Mulyasuryani; Akhmad Sabarudin (The Journal of Pure and Applied Chemistry Research, 2013)
The adsorption process depends on initial concentration of Cd2+ and ratio of  chitosan in adsorbent. The present study deals with the competitive adsorption of Cd2+ ion onto silica graft with chitosan. Batch adsorption experiments were performed at five different initial Cd2+ concentrations (5, 10, 15, 20 and 25 ppm), on five different proportion from silica to chitosan (100%, 95%, 85%, 75% and 65%) as adsorbent at pH 5. In the recovery process, the high recovery at 0.5 mg and observed the recovery decrease with increasing the initial concentration of Cd2+, and the low recovery at 0.25 mg from Cd2+. In this study, the adsorption capacity of Cd2+ in regard to the ratio of silica and chitosan hybrid adsorbents are examined in detail. The aim of this study to explore effects of initial concentrations of Cd2+, and the ratio of silica to chitosan on the adsorption and recovery of Cd2+.